The Homo Deus Protocol & The Interplay of Android Science Fiction and Theories of Emotion - Nelson, Mathew (Curtin University, 2024)
My PhD project investigates the interplay of android science fiction and theories of emotion to critique classical perspectives of emotion in favour of a constructionist framework. This project analyses the context and representations of androids in science fiction by drawing upon scholarship from science fiction studies in conjunction with robotics and emotion psychology. I propose new possibilities of understanding and agency for android characters and the android–human relationship in this subgenre of science fiction.